Methane production and characteristics of the microbial community in the co-digestion of spent mushroom substrate with dairy manure. (February 2018) - Luo, Xiaosha; Yuan, Xufeng; Wang, Shiyu; Sun, Fanrong; Hou, Zhanshan; Hu, Qingxiu; Zhai, Limei; Cui, Zongjun; Zou, Yajie
Highlights: Co-digestion of spent mushroom substrate and dairy manure was investigated. Co-digestion resulted in methane yield higher than individual substrates. Methanosaetaceae was the predominant methanogens during the co-digestion. Abstract: Spent mushroom substrate (SMS) is a potential biomass material generated during mushroom cultivation. In this study, the methane yield and microbial community resulting from co-digestion of SMS and dairy manure (DM) at different mixing ratios (0:4, 1:1, 3:1, and 1:3), were evaluated. Co-digestion analysis showed that the methane yield from the mixtures was 6%–61% higher than the yield from SMS or DM alone, indicating a synergistic effect of co-digestion of SMS with DM. For the SMS of F.velutipes (SFv) and P.erygii var. tuoliensis (SPt), co-digestion of DM/SMS at a ratio of 1:1 was optimal, but for the SMS of P. eryngi (SPe), co-digestion of DM/SMS at a ratio of 3:1 was ideal. The pH at all co-digestion ratios was in the range of 6.8–8.0, indicating that adding DM could increase the systemic buffering capacity. Methanosaetaceae was shown to be the predominant methanogens present during the co-digestion of DM/SMS.